Managing Bigeye Tuna in the Western and Central Pacific Ocean - Post, Valerie; Squires, Dale (Frontiers in Marine Science, 2020)
The Western and Central Pacific Fisheries Commission (WCPFC) is responsible for managing highly migratory species in the Western and Central Pacific Ocean (WCPO), and has been interested in managing bigeye tuna as stock assessments prior to 2017 indicated that the stock was experiencing overfishing. This paper provides some background on the primary fisheries catching bigeye tuna in the WCPO, describes the various policies within the conservation and management measures adopted by the WCPFC, discusses the effectiveness of such policies, and concludes with some suggestions for future policies for consideration.